2017
DOI: 10.1200/jco.2016.69.7946
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Adolescent and Young Adult Patients With Cancer: A Longitudinal Study

Abstract: Purpose To examine changes in health-related quality of life (HRQoL) and its predictors during the first 2 years after initial cancer diagnosis in adolescent and young adult (AYA) patients with cancer. Patients and Methods A multicenter, longitudinal, prospective study was conducted among a diverse sample of AYA patients with cancer ages 15 to 39 years. One hundred seventy-six patients (75% response) completed a self-report measure of HRQoL (Short Form-36 [SF-36]) within the first 4 months after diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 18 publications
5
88
1
4
Order By: Relevance
“…Patients with sarcoma were reported to have lower outcomes at all disease phases compared with the general population, despite showing improvements in HRQoL during follow‐up. This is similar to results noted for other malignancies . Patients treated for sarcoma typically reported issues with their role and social functioning, as well as fatigue, insomnia, pain, loss of appetite, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sarcoma were reported to have lower outcomes at all disease phases compared with the general population, despite showing improvements in HRQoL during follow‐up. This is similar to results noted for other malignancies . Patients treated for sarcoma typically reported issues with their role and social functioning, as well as fatigue, insomnia, pain, loss of appetite, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the few studies who examine psychological distress of AYAs with cancer have found that every fourth patient exceeds distress cutoff values during and after medical treatment . Furthermore, AYAs with cancer who have completed medical treatment are more distressed than age‐matched healthy controls . As far as sociodemographic (eg, gender, age at diagnosis) and medical (eg, treatment status) correlates of psychosocial distress are concerned, current research findings have, to date, been inconsistent…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Being sick with cancer during this sensitive time often results in multiple physical, psychological, and psychosocial limitations such as infertility, 8 changes in physical appearance, 9 fatigue, 10 and disruptions in social life and career. 12,13 Cancer November 15, 2018 QOL is a broad multidimensional concept that usually includes subjective evaluations of both positive and negative aspects of life. Because psychological symptoms such as anxiety and distress develop differently after cancer and are highly interconnected with psychosocial factors, we believe it is safe to assume that QOL also is quite likely to change over time.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] LS refers to a subjective appraisal of one's personal life in an number of life domains. 20 These frequently lack some important and unique concerns of AYA patients with cancer such as employment challenges, fertility and family planning, or body image, 13,20,21 yet all these domains are likely to be affected by illness, especially in AYA patients. It can be considered as an indicator of QOL because it reflects how satisfied one is with one's life as a whole.…”
Section: Introductionmentioning
confidence: 99%